2014
DOI: 10.1088/0004-637x/793/2/111
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHELHIFI OBSERVATIONS OF O2TOWARD ORION: SPECIAL CONDITIONS FOR SHOCK ENHANCED EMISSION

Abstract: We report observations of molecular oxygen (O 2 ) rotational transitions at 487 GHz, 774 GHz, and 1121 GHz toward Orion Peak A. The O 2 lines at 487 GHz and 774 GHz are detected at velocities of 10-12 km s −1 with line widths ∼3 km s −1 ; however, the transition at 1121 GHz is not detected. The observed line characteristics, combined with the results of earlier observations, suggest that the region responsible for the O 2 emission is 9 (6 × 10 16 cm) in size, and is located close to the H 2 Peak 1 position (wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 61 publications
3
42
1
Order By: Relevance
“…The quoted line widths (FWHMs) are only lower limits because of the difficulty in accurately determining the local continuum on sloping backgrounds. These HOOH widths are smaller than those for O 2 reported by Chen et al (2014). The 252 GHz line was not detected.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…The quoted line widths (FWHMs) are only lower limits because of the difficulty in accurately determining the local continuum on sloping backgrounds. These HOOH widths are smaller than those for O 2 reported by Chen et al (2014). The 252 GHz line was not detected.…”
Section: Resultscontrasting
confidence: 73%
“…Goldsmith et al 2000;Pagani et al 2003), with the definite detection of the molecule in merely two sources, viz. ρ Oph A (Larsson et al 2007;Liseau et al 2012) and Orion A (Goldsmith et al 2011;Chen et al 2014). Some cases have been either resolved or remained undecided (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(Goldsmith et al 2000) and Odin (Pagani et al 2003) spacecrafts, counterbalanced by a single detection in ρ Ophiuchi (Larsson et al 2007) with Odin, we detected O 2 towards Orion (Goldsmith et al 2011) and confirmed the detection towards ρ Ophiuchi, (Liseau et al 2012). However, the location of the emission in Orion is ill-defined and that made the interpretation of the observations difficult (Goldsmith et al 2011;Chen et al 2014;Melnick & Kaufman 2015). This is despite the rare velocity value of 11.3 km s −1 , which should have limited the probable emission region to a few spots at the same LSR velocity as traced by the NH 3 (6, 6) inversion transition (Goddi et al 2011).…”
Section: Non-detection Of Species In Orionsupporting
confidence: 72%
“…Two pointing directions were observed, the same as those used in the Herschel observations (Goldsmith et al 2011;Chen et al 2014), namely the KL region, RA J2000 : 05 h 35 m 14 s .160, Dec J2000 : −05 • 22 31 . 504 and the H 2 vibrational peak farther north, RA J2000 : 05 h 35 m 13 s .477, Dec J2000 : −05 • 22 08 .…”
Section: Observations and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation